2017
DOI: 10.18844/cjes.v12i4.2902
|View full text |Cite
|
Sign up to set email alerts
|

Scale of professional ethics for individuals working in the field of special education: validity and reliability study

Abstract: Professional ethics includes the principles set forth by professional associations and accepted as correct by discussions over time, and which has become the sine qua non of a profession today. Professional ethics are established to increase the quality of professional practices and ensure correct and honest conduct. Not having professional ethical principles for the special education field negatively affects the quality of services. The purpose of this study was to develop a scale of principles in professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Another commonly occurring ethical dilemma associated with learners who have special educational needs includes services provided by teachers who received inadequate training in special education (Akcamete, Kayhan, & Yildirim, 2017). It has been found that teachers supporting learners with special educational needs lack the necessary expertise to educate learners with a range of disabilities (Khumalo & Hodgson, 2017).…”
Section: Learners With Special Educational Needs As An Ethical Impera...mentioning
confidence: 99%
“…Another commonly occurring ethical dilemma associated with learners who have special educational needs includes services provided by teachers who received inadequate training in special education (Akcamete, Kayhan, & Yildirim, 2017). It has been found that teachers supporting learners with special educational needs lack the necessary expertise to educate learners with a range of disabilities (Khumalo & Hodgson, 2017).…”
Section: Learners With Special Educational Needs As An Ethical Impera...mentioning
confidence: 99%
“…This was followed by that "in creating a just school climate, principals must have the courage to adhere to ethical standards" with mean score of 3.98 and ranked 2 nd and "principal must be committed to the other principles of organizational justice, as a commitment to an ethical principle of fairness" got mean score of 3.95 in ranked 3 rd . Ethics is a scientific discipline that tries to create ideals and norms by questioning the moral behaviors and aims to help individuals, institutions, and experts make decisions by enabling them to distinguish right from wrong (Akcamete & Yildirim, 2017). As a whole, the ethical principle got weighted mean score of 3.96 and a verbal interpretation of "Always Complied With".…”
Section: 7mentioning
confidence: 99%
“…On the other hand, mainstreaming and inclusive practices have increased in recent years and students with special needs have the opportunity to receive education with their peers and participate in social life more frequently (Gozun and Yikmis, 2004;Kaya et al, 2017). In order to meet the educational needs of individuals in need of special education, instructional practices are adapted for them in line with their diagnosis, disability characteristics and needs (Akcamete, Kayhan and Yildirim, 2017;Ozcan and Merdan, 2016).…”
Section: Introductionmentioning
confidence: 99%